2018
DOI: 10.1016/j.linged.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Korean–English bilingual sibling interactions and socialization

Abstract: This paper examines how a pair of Korean-American siblings interact and socialize and how their interactions change over time as the younger sibling starts to go to an Englishspeaking preschool. A 7-year-old Korean-English bilingual girl and her 3-year-old sister were observed in their home over 23 visits within a year. Their discourse data, including 33 h of audio-recordings, were analyzed from the Language Socialization perspective. The older sibling's authority derived from the age-based Korean family hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Second, due to limited space, this work does not include data the first author collected from the child’s home (Cho, 2018). How children construct and negotiate their ethnic identities might be different between home and school (Huang and Stormshak, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Second, due to limited space, this work does not include data the first author collected from the child’s home (Cho, 2018). How children construct and negotiate their ethnic identities might be different between home and school (Huang and Stormshak, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Besides parents, the major "influencers" in the heritage language maintenance in immigrant families are siblings (Duursma et al, 2007;Cho, 2018). For example, children in Chinese Singaporean families speak more Mandarin than English with their siblings, particularly with younger ones (Cavallaro et al, 2021).…”
Section: Child Bi/multilingualism In Immigration Contexts and Familymentioning
confidence: 99%
“…The literature on sibling talk, and by extension on peer talk, has shown that interactions between children are important loci for learning (Goodwin and Kyratzis 2007;van der Schaaf 2016). With regard to siblings, research has shown older siblings do a lot of direct language teaching and play word games with younger siblings (Blum-Kulka and Snow 2004;Cho 2018;Goodwin and Kyratzis 2007). Sibling talk and peer talk, however, also socialize children beyond linguistic skills.…”
Section: Socialization In Families and Among Childrenmentioning
confidence: 99%
“…Much research on socialization in sibling interaction above thus often suggests there are relatively fixed roles of socialization argent and target, in which the eldest usually is the agent and the younger sibling the target. However, longitudinal research has also shown that processes of socialization between siblings also change as children grow older; younger siblings take increasingly active roles in sibling dyads, initiating more games, cooperating and participating more in joint play, and become more effective in using their understanding of power in situations of conflict (Cho, 2018;Dunn, 2015). Dunn (2015) points out this is intricately connected to a change in power relations, but that it remains unclear what this exactly means for the siblings' abilities to influence one another, and establishing dominance in interaction.…”
Section: Socialization In Families and Among Childrenmentioning
confidence: 99%
See 1 more Smart Citation